Produksi dan Kualitas Benih Kedelai dalam Sistem Produksi Bersih - Hartawan, Rudi; Nengsih, Yulistiati; Marwan, dan Edy (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Production of high quality seed is one of the key factors for soybean self-sufficiency. The study was aimed to produce high quality soybean seed from zero waste system. The trial was carried out at Sebapo Experimental Station, Jambi, Center for Agricultural Post Harvest Research and Development, and Center for Agricultural Land Resources Research and Development, The Ministry of Agriculture, Bogor, from January until October 2017. The experiment used a complete randomized design with a treatments combination both organic nutrient of composted soybean litter (5 tons ha-1) and inorganic nutrient (25 kg Nitrogen ha-1, 50 kg P2O5 ha-1, and 50 kg K2O ha-1). The treatments were designed as follow : K0 (control), K1 (100% organic), K2 (75% organic + 25% inorganic), K3 (50% organic + 50% inorganic), K4 (25% organic + 75% inorganic), and K5 (100% inorganic). The results showed that the treatment K3 produced the highest seed production (1.72 tons ha-1) and the highest 1,000 seed weight (147.71 g). After 3 months storage at room temperature, the seed with treatment K3 could maintain its quality with indicator 1,000 seed weight (140.98 g), 10.82% water content, 34.98% protein content, 57.42 μScm-1g-1 electrical conductivity, 80.98% germination percentage and 27.48% etmal-1 rate of germination speed.Keywords: Compost, litter, seed technology